The Importance of Islamic Education and Gender Equality in Contemporary Schools - Hairiyah, Hairiyah; Sirait, Sangkot; Arif, Mahmud (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
This article discusses the importance of education, particularly Islamic Religious Education, in addressing gender issues and inequalities faced by women in various aspects of life. Gender, as a social construction, is different from biological sex and plays an important role in social and cultural dynamics. This research, which is descriptive-critical in nature, uses a literature approach to analyze data sources and related literature. The main focus is on how education, especially Islamic religious education, can be used as a tool to combat ingrained gender prejudices and stereotypes in society. Islamic Educationis seen as a means to spread the values of equality, freedom, democracy and justice, and to overcome gender-biased interpretations of religious texts. The article emphasizes the importance of an inclusive and gender justice based curriculum in shaping young people's attitudes and understanding of gender issues. This includes addressing gender stereotypes in educational materials and promoting critical thinking among students. In addition, this article highlights the need to recognize that the challenges in realizing gender equality lie not only in education, but also in social and cultural practices. Therefore, it is proposed that gender justice-based Islamic Educationcan be a catalyst in promoting a more balanced and inclusive understanding of gender roles, which is essential for the development of a more tolerant, just and egalitarian society.